THEOPHIL ANDREEVICH YEROFEYEV – FOUNDER OF THE FIRST OPHTHALMOLOGY CLINICS IN SIBERIA (170 ANNIVERSARY AND 120 YEARS EYE CLINIC) - G. I. Mendrina; L. A. Mochalina (Бюллетень сибирской медицины, 2014)
Theophil A. Yerofeyev – the first ophthalmologist in Siberia, he was founder and first head of the Department and Clinic of Ophthalmology in The Imperial Tomsk University, the first organizer of the eye units, allowed to bring qualified specialized assistance to the population, especially agriculture. Department of Ophthalmology and Clinic of the Tomsk University began training and organizational consulting center for Siberia and Far East.